Power effects, normalising advice and evolving knowledge of doctoral writing - Gormley, Kevin; Mochizuki, Naoko (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2023)
Prescriptive advice about doctoral writing often fails to recognise the complexities of the doctoral journey. Linguistic and cultural backgrounds are negated where advice about writing converges around a norm. In this paper, we explore the role of ‘advice’ in our growth as thesis writers by examining our literacy history and tensions we faced while writing our theses. We pursue a duoethnographic process (Sawyer & Norris, 2013), a process that facilitates the construction and reconstruction of perspectives. From our differing backgrounds, we experienced discourses of ‘advice’ in alternative ways. We identify opposing 'advice' trends which, in turn, provided a space for our agency. Inspired by Foucault’s (1977) ‘power/knowledge’ we think of past experiences and encounters along our doctoral journey as power effects which shaped our views on advice. We conclude by outlining how insights for our teacher-selves inform how we speak about impacts and advice with doctoral students.